A SEMIOTICS STUDY ON SLOGAN AND PICTURE OF A MILD ADVERTISEMENT BUKAN BASA BASI RED BOX VERSION - AZMI, KHOIRIL (Jurnal Ilmiah Mahasiswa FIB, 2014)
Communication can be done in some ways, using either verbal communication ornon-verbal  communication.  Verbal  communication  uses  language  and  non-verbalcommunication is non-linguistic communication. Non- linguistics communication canbe done using signs, signals, or symbols (Mulyana,2000,p.308). Sign is somethingthat can be interpreted as having a meaning, therefore it is able to convey informationto someone. So, the sign serves as a conduit of meaning to the message that is formedand  can  be  conveyed  to  the  readers.  In  this  study,  the  researcher  conducts  thesemiotics  analysis  in  the  advertisement  of  A Mild  “Bukan Basa Basi”  Red  Boxversion. This study answers three problems, namely: (1) What are the signs found inthe advertisement (2) What are the meanings of the signs in advertisement and (3) How the signs support the idea of the advertisement.This study uses Peirce theory of triadic model as follows icon, index and symbol. This  research is  a  qualitative  research  to  comprehend the  phenomena about  whathappened  to  the  research’s  subject  such  as  behavior,  perception,  motivation  andaction. The researcher conducts content or document analysis to analyze the signsused in advertisement of A Mild “Bukan Basa Basi” Red box version.This study reveals that some signs represent the content of the advertisement. There are  signs  that  exemplified by Peircean applied in  advertisement  of A Mild "Bukan Basa Basi" Red box version. In the six advertisements, signs of the icon, index and symbol are found of A Mild "Bukan Basa Basi" Red Box version. Thesigns found are the icons of the image description that represents the meaning of the index which is the tagline of the advertisement. Where in each advertisement of A Mild "Bukan Basa Basi" red box version, the icon and the index has a correlation inthe  form of  an  understanding,  supported  by  a  symbol  which  is  the  slogan  as  areinforcement  of  the  meaning  description  of  icon  and  index.  In  addition,  the  six advertisements of A Mild "Bukan Basa Basi" Red box version have the same patternin characteristic application of image layout, tagline and slogan.The researcher suggests the next researchers broaden the semiotics scope such asanalyze other objects, such as logos, brand products, or the cover of music. Keywords: semiotics,  sign,  advertisement,  A Mild  "Bukan  Basa  Basi" Red  Boxversion.